Plants of Boreh Materials for Rematic Disease (Tuju) in Taro Village, Tegallalang District, Gianyar Regency - Riantini, Ni Wayan Ayu; Kriswiyanti, Eniek; Sudiartawan, I Putu (Metamorfosa: Journal of Biological Sciences, 2019)
Research this it directions for knowing type tuju disease, plants type, parts of plant for tuju disease in Taro Village, District Tegallalang, Regency Gianyar. This Research was held at 14 Banjar with every single one of banjar taken by 5 heads of family, until the sample of research become to 70 head of families. The method used in research this is snowball sampling and purposive sampling. Based on the results of the research indicated 6 type of tuju disease at Taro village. Type of tuju disease that I found is tuju ayan, tuju desti, tuju moro, tuju gatal, tuju ucing-ucing, and tuju wind. Type herbs found as many as 38 species plants that cover 22 families, with the most widely from family Zingiberaceae (7 species). Part plants used as ingredients boreh is stem, flower, fruit, rhizome, tuber, leaf, skin stem, root and seeds. Most part used is part leaves.